Calculation of Resonance S-Matrix Poles by Means of Analytic Continuation in the Coupling Constant (Communications in Computational Physics, 2018)
The method of analytic continuation in the coupling constant in combinationwith the use of statistical Padé approximation is applied to the determination ofcomplex S-matrix poles, i.e. to the determination of resonance energy and widths.These parameters are of vital importance in many physical, chemical and biologicalprocesses. It is shown that an alternative to the method of analytic continuation inthe coupling constant exists which in principle makes it possible to locate several resonancesat once, in contrast to the original method which yields parameters of onlyone resonance. In addition, the new approach appears to be less sensitive to the choiceof the perturbation interaction used for the analytical continuation than the originalmethod. In this paper both approaches are compared and tested for model analyticseparable potential. It is shown that the new variant of the method of analytic continuationin the coupling constant is more robust and efficient than the original methodand yields reasonable results even for data of limited accuracy.